Protoneutron star evolution and the neutrino-driven wind in general relativistic neutrino radiation hydrodynamics simulations - Fischer, T.; Whitehouse, S. C.; Mezzacappa, A.; Thielemann, F.-K.; Liebendörfer, M. (Astronomy and astrophysics (Berlin), 2010)
Massive stars end their lives in explosions with kinetic energies on the order of 1051 erg. Immediately after the explosion has been launched, a region of low density and high entropy forms behind the ejecta, which is continuously subject to neutrino heating. The neutrinos emitted from the remnant at the center, the protoneutron star (PNS), heat the material above the PNS surface. This heat is partly converted into kinetic energy, and the material accelerates to an outflow that is known as the neutrino-driven wind. For the first time we simulate the collapse, bounce, explosion, and the neutrino-driven wind phases consistently over more than 20 s. Our numerical model is based on spherically symmetric general relativistic radiation hydrodynamics using spectral three-flavor Boltzmann neutrino transport. In simulations where no explosions are obtained naturally, we model neutrino-driven explosions for low- and intermediate-mass Fe-core progenitor stars by enhancing the charged current reaction rates. In the case of a special progenitor star, the 8.8 $M_\odot$ O-Ne-Mg-core, the explosion in spherical symmetry was obtained without enhanced opacities. The post-explosion evolution is in qualitative agreement with static steady-state and parametrized dynamic models of the neutrino-driven wind. On the other hand, we generally find lower neutrino luminosities and mean neutrino energies, as well as a different evolutionary behavior of the neutrino luminosities and mean neutrino energies. The neutrino-driven wind is proton-rich for more than 10 s and the contraction of the PNS differs from the assumptions made for the conditions at the inner boundary in previous neutrino-driven wind studies. Despite the moderately high entropies of about 100 kB/baryon and the fast expansion timescales, the conditions found in our models are unlikely to favor r-process nucleosynthesis. The simulations are carried out until the neutrino-driven wind settles down to a quasi-stationary state. About 5 s after the bounce, the peak temperature inside the PNS already starts to decrease because of the continued deleptonization. This moment determines the beginning of a cooling phase dominated by the emission of neutrinos. We discuss the physical conditions of the quasi-static PNS evolution and take the effects of deleptonization and mass accretion from early fallback into account.